Cover and Table of Content - Wijaya, I Made Saka (Jurnal Biologi Udayana; Vol 24 No 2 (2020): JURNAL BIOLOGI UDAYANA, 2020)
Cover, Editor, and Table of Content for JBIOUNUD volume 24 number 2, December 2020